Dannelse og samskaping av utdanning mellom akademia og sykehjem - Gunilla Kulla; Åshild Slettebø (Septentrio Academic Publishing, 2020)
Cultivation and co-creation of education between academy and nursing home - a critical ethnography study   Collaboration between academy and practice in education is emphasized. In this study, we explored and described boundary-crossing spaces, when co-creating an adjusted educational program for nursing students in a nursing home in Norway. Our aim was to explore how to learn person-centered dementia care through the participants in a learning community. A critical ethnographic approach and method with observations, field n otes, minutes of board, spontaneous meetings, and focus groups particularly with the students were used. Data were analyzed with six-step thematic analysis by Braun and Clarke. There were two main themes: 1) Creating a room for learning communities and 2) The room of the cultivation and border-crossing in learning communities. We further suggest, learning communities' co-creation in elderly care, might potentiate innovative research and development methods for the future.